The Relationship Between Nutrition Knowledge and Dietary Abstinence Attitudes During the Postpartum Period - Dara Mila Revalina; Yanti Srinayanti; Ima Sukmawati; Elis Roslianti; Aulia Ridla Fauzi; Dini Ariani (LPPM STIKes Muhammadiyah Ciamis, 2026)
Purpose: The purpose of this study is to analyze the relationship between nutritional knowledge and attitudes toward food abstinence among postpartum mothers. Methods: This study employed a quantitative research design with a cross-sectional approach. Postpartum mothers in the working area of the UPTD Sadananya Community Health Center were selected using purposive sampling techniques. Data were collected using a structured questionnaire distributed through Google Forms to assess respondents’ nutritional knowledge and attitudes toward food restrictions. Data analysis was conducted using the Chi-Square test with a specified significance level. Results: The results showed that the majority of respondents had good nutritional knowledge and a positive attitude toward consuming nutritious foods. Statistical analysis indicated a significant relationship between nutritional knowledge and attitudes toward food abstinence. Respondents with higher levels of knowledge tended to demonstrate more rational behavior in food selection during the postpartum period. Conclusions: There is a significant relationship between nutritional knowledge and attitudes toward food abstinence among postpartum mothers. Therefore, continuous health education by healthcare professionals is essential to improve mothers’ understanding of balanced nutrition, support postpartum recovery, and promote the health of both mother and baby.